2018
DOI: 10.1021/acsami.8b12966
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt Phosphate Nanostructures for Non-Enzymatic Glucose Sensing at Physiological pH

Abstract: Nanostructured materials have great potential as platforms for analytical assays and catalytic reactions. Herein, we report the synthesis of electrocatalytically active cobalt phosphate nanostructures (CPNs) using a simple, low-cost, and scalable preparation method. The electrocatalytic properties of the CPNs toward the electrooxidation of glucose (Glu) were studied by cyclic voltammetry and chronoamperometry in relevant biological electrolytes, such as phosphate-buffered saline (PBS), at physiological pH (7.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 75 publications
1
35
0
Order By: Relevance
“…Transition metals are low cost and can be used as electrocatalytic materials for glucose. There are many electrocatalysts reported for transition metals, including pure metals [6,25], bimetals [7,26,27,28], compounds [29,30,31,32], and composites [33,34,35,36,37,38,39,40,41,42,43,44] for non-enzymatic glucose sensors. The catalytic principle of non-enzymatic glucose sensors based on transition metals is by using the d-electron of d-orbital to form medium-strength bonds with substrates, so that the analyte can be easily adsorbed at any time, and its products can be easily desorbed [3].…”
Section: Introductionmentioning
confidence: 99%
“…Transition metals are low cost and can be used as electrocatalytic materials for glucose. There are many electrocatalysts reported for transition metals, including pure metals [6,25], bimetals [7,26,27,28], compounds [29,30,31,32], and composites [33,34,35,36,37,38,39,40,41,42,43,44] for non-enzymatic glucose sensors. The catalytic principle of non-enzymatic glucose sensors based on transition metals is by using the d-electron of d-orbital to form medium-strength bonds with substrates, so that the analyte can be easily adsorbed at any time, and its products can be easily desorbed [3].…”
Section: Introductionmentioning
confidence: 99%
“…In the voltammetric and amperometric experiments, NaOH was chosen as supporting electrolyte because the glucose oxidation reaction catalyzed by transition metal oxides was more favorable in alkaline media . In the preliminary tests, we found that the increase of NaOH concentration lowered the over potential assuredly for glucose oxidation, but also speeded up the oxygen evolution reaction which constrained the operational potential range otherwise.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that the LOD and detection range of the engineered sensing system are within the physiological concentration range of Glu in healthy and diabetic patients (1-30 × 10 −3 m). [24] In addition, to test the selectivity of the system towards glucose, the emission intensity of DAP was studied after the addition of other sugars such as lactose (1.5 × 10 −6 m), fructose (0.1 × 10 −3 m) and galactose (3 × 10 −6 m). Figure S8 (Supporting Information) shows an increase in emission intensity as a function of time, when Cu-DS microparticle were incubated with 1.5 × 10 −3 m Glu, OPD, GOx, in PBS.…”
Section: High-throughput Detection and Sensing Of H 2 O 2 And Glumentioning
confidence: 99%